1991
DOI: 10.1136/adc.66.4.532
|View full text |Cite
|
Sign up to set email alerts
|

High mebendazole doses in pulmonary and hepatic hydatid disease.

Abstract: Thirty nine children with 71 hydatid cysts were given mebendazole orally in a dose of 100-200 mg/kg/day for 12 weeks and were followed up for a mean (SD) of 63 (24) (67) 10 (27) Improvement (%) 2 (6) 11 (30) Failure (%) 9 (27) 16 (43) 'Tere was one cyst found in the spleen, which did not respond to treatment.differences were also found in the hepatic cysts (3-93 (1-87) and 7-78 (3 08) cm, respectively, p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 4 publications
0
20
1
Order By: Relevance
“…In general, drug penetration into the cyst is in reverse proportion to the thickness of the pericystic fibrous capsule that is thinner in children when compared to adults. For the same reason, children respond to medical treatment better than adults [10,11]. However, in all our cases, the cyst size was greater than 6 cm.…”
Section: Discussioncontrasting
confidence: 51%
“…In general, drug penetration into the cyst is in reverse proportion to the thickness of the pericystic fibrous capsule that is thinner in children when compared to adults. For the same reason, children respond to medical treatment better than adults [10,11]. However, in all our cases, the cyst size was greater than 6 cm.…”
Section: Discussioncontrasting
confidence: 51%
“…It is noteworthy that in some human trials MBZ achieved lower plasma levels than in mice as the amino and hydroxy metabolites reached two- to ten-fold the plasma levels of the parental MBZ (24, 25), which could indicate higher metabolic enzyme activities in human. Thus, much higher doses up to 200 mg/kg/day could be tolerated in human and should be used in future human brain tumor therapy (26). …”
Section: Discussionmentioning
confidence: 99%
“…[23] High dose treatment with mebendazole 100 to 200 mg/kg/day for 3 months has also been used in children successfully and without serious adverse effects. [1] Messaritakis et al [24] treated 39 paediatric patients with mebendazole 100 to 200 mg/kg/day for 12 weeks and found that 23 of them were cured. Mebendazole 50 to 200 mg/kg/day for 6 weeks was also given to patients aged between 10 and 72 years who were ineligible for surgery; 50% of these patients were cured.…”
Section: Mebendazolementioning
confidence: 99%